2021
DOI: 10.1080/16000870.2021.1966869
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of modified Hargreaves equation for precise estimation of reference evapotranspiration

Abstract: There are a lot of meteorological stations around the world, like Pakistan, where all the meteorological parameters are not accessible to analyze Penman-Monteith (PM) method for the estimation of Reference Evapotranspiration (ET o ). So ablative methods such as Hargreaves Samani (HS) equation are therefore a potential solution to this problem, which required small numbers of meteorological parameters to estimate ET o . But, simplification brings imprecision and the need for regional calibration of the HS equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…The monthly, seasonal, and annual observations found that RF estimated better than other models. The trend of estimated ET 0 by the modi ed Hargreaves-Samani model was similar to the previous study done around the globe (Trajkovic 2007, Habeeb et al, 2021, Gentilucci et al 2021). The growth and yield of the maize and wheat crops were found to be comparable for both treatments.…”
Section: Calibration and Validation Modelssupporting
confidence: 87%
“…The monthly, seasonal, and annual observations found that RF estimated better than other models. The trend of estimated ET 0 by the modi ed Hargreaves-Samani model was similar to the previous study done around the globe (Trajkovic 2007, Habeeb et al, 2021, Gentilucci et al 2021). The growth and yield of the maize and wheat crops were found to be comparable for both treatments.…”
Section: Calibration and Validation Modelssupporting
confidence: 87%
“…Some of the input data used for ET estimation were based on assumptions. Moreover, Habeeb et al [47] evaluated the performance of the Hargreaves method and its modified version in estimating ET in Pakistan. They showed the modified Hargreaves method performs better than its original version in estimating ET in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…A python script was written to serve this purpose. Three methods were covered in the detection, i.e., Pettitt test (Mallakpour & Villarini, 2016), Buishand U test (Habeeb et al, 2021), and Standard Normal Homogeneity test (SNHT) (Pohlert, 2020). These tests were applied in the two time series of HMI values of magazines and newspapers.…”
Section: Change Point Detectionmentioning
confidence: 99%